Chemical and Microbiological Evaluation of Pasteurized Milk Available in Sylhet City of Bangladesh (The Agriculturists, 2012)
A study was conducted to evaluate the chemical and microbiological quality of pasteurized milk samples belonging to five brands: Milk vita, Tatka, Farm Fresh, Aarong and RD milk. Pasteurized milk of different brands were collected from the retail store of Sylhet city and the laboratory examination was conducted at Dairy Science Laboratory under the Dept. of Dairy and Poultry Science, Sylhet Agricultural University, Bangladesh during January to march 2012. The average fat contents were 3.51, 3.06, 3.26, 3.41 and 3.33 for Milk vita, Tatka, Farm Fresh, Aarong and RD milk brands respectively. There was significant difference among the different brands pasteurized milk in respect of fat%. The protein contents were 4.07, 4.14, 4.14, 4.03 and 4.10 respectively in Milk vita, Tatka, Farm Fresh, Aarong and RD milk brands, though the difference was not significant. The equivalent SNF contents were 8.13, 8.54, 8.15, 8.11 and 8.02%, whereas total solids were 11.46, 11.58, 11.41, 11.53 and 11.35%, respectively. Acidity content of different brands of pasteurized milk was highly significant (p